2005
DOI: 10.1161/01.cir.0000151308.06673.d2
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Flow-Mediated Dilation and Risk of Restenosis in Patients Undergoing Coronary Stent Implantation

Abstract: Background-Impaired endothelial function is a key event in the atherosclerosis process and predicts future cardiovascular events in subjects with and without coronary artery disease (CAD). We performed the first prospective study evaluating whether early measurement of brachial artery endothelium-dependent dilation (flow-mediated dilation [FMD]) after coronary stenting could predict occurrence of in-stent-restenosis. Methods and Results-The study population included 136 patients with single-vessel CAD undergoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
110
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(120 citation statements)
references
References 30 publications
6
110
1
3
Order By: Relevance
“…Recent meta‐analyses have shown that FMD is a significant predictor of cardiovascular events independent of conventional cardiovascular risk factors 12, 13, 14. However, there have been very few studies in which the predictive value of FMD in patients with established CAD was investigated 29, 30. In addition, the predictive value of FMD in patients with high risk for cardiovascular events is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Recent meta‐analyses have shown that FMD is a significant predictor of cardiovascular events independent of conventional cardiovascular risk factors 12, 13, 14. However, there have been very few studies in which the predictive value of FMD in patients with established CAD was investigated 29, 30. In addition, the predictive value of FMD in patients with high risk for cardiovascular events is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The endothelial function is noninvasively quantified according to the FMD of the brachial artery, which has been shown to be inversely associated with the risk of future cardiovascular events [17][18][19] . Previous studies have demonmm) groups; therefore, the results for %FMD obtained in the present study appear to reflect the actual vasodilatory potency.…”
Section: Discussionmentioning
confidence: 99%
“…Исследование ARMYDA-150 продемонстрировало дозозависимый эффект клопи-догрела на реактивность плечевой артерии: лечение в дозе 150 мг/день ассоциировалось со статистически значимым улучшением ПЗВД и снижением на 42% доли больных с нарушенной реактивностью плечевой арте-рии (ПЗВД<7%) по сравнению с лечением в дозе 75 мг/день. С учетом данных о связи повышенного рис-ка рестеноза металлического стента без лекарственно-го покрытия (а теоретически и с лекарственным по-крытием) с дисфункцией эндотелия у перенесших ЧКВ больных [23] наши данные могут оказать влияние на практические рекомендации в отношении схемы под-держивающей терапии. Необходимы дальнейшие ис-следования, чтобы определить, связано ли улучшение функции эндотелия при приеме клопидогрела в высокой дозе с ингибированием активности тромбоцитов или с прямым влиянием на эндотелиальные P2Y 12 рецеп-торы [32].…”
Section: Discussionunclassified
“…Анализировались пять сердечных циклов и определялись средние результаты для каждого изображения. В нашем предыдущем проспективном исследовании [23] у больных, подвергающихся ЧКВ с установкой металлического стента без лекарственного покрытия, нарушенная функция эндотелия, опреде-Сравнение высоких и стандартных поддерживающих доз клопидогрела после ЧКВ лявшаяся как ПЗВД <7%, ассоциировалась с повы-шением риска рестеноза стента в 4,5 раза при отда-ленном наблюдении, тогда как ПЗВД ≥7% имела 96%-ное отрицательное предсказательное значение в отношении развития рестеноза.…”
Section: материал и методыunclassified